Transcriptome analysis revealed the genes and major pathways involved in prunetrin treated hepatocellular carcinoma cells - Abusaliya, Abuyaseer; Kim, Hun Hwan; Vetrivel, Preethi; Bhosale, Pritam Bhagwan; Jeong, Se Hyo; Park, Min Yeong; Lee, Si Joon; Kim, Gon Sup (Frontiers in Pharmacology, 2024)
Liver cancer represents a complex and severe ailment that poses tough challenges to global healthcare. Transcriptome sequencing plays a crucial role in enhancing our understanding of cancer biology and accelerating the development of more effective methods for cancer diagnosis and treatment. In the course of our current investigation, we identified a total of 1149 differentially expressed genes (DEGs), encompassing 499 upregulated and 650 downregulated genes, subsequent to prunetrin (PUR) treatment. Our methodology encompassed gene and pathway enrichment analysis, functional annotation, KEGG pathway assessments, and protein-protein interaction (PPI) analysis of the DEGs. The preeminent genes within the DEGs were found to be associated with apoptotic processes, cell cycle regulation, the PI3k/Akt pathway, the MAPK pathway, and the mTOR pathway. Furthermore, key apoptotic-related genes exhibited close interconnections and cluster analysis found three interacting hub genes namely TP53, TGFB1 and CASP8. Validation of these genes was achieved through GEPIA and western blotting. Collectively, our findings provide insights into the functional landscape of liver cancer-related genes, shedding light on the molecular mechanisms driving disease progression and highlighting potential targets for therapeutic intervention. Deleted: Transcriptome sequencing assumes a pivotal role in 40 augmenting comprehension of cancer biology and expediting the 41 formulation of more efficacious modalities for cancer diagnosis and